Fabrication of a hollow sphere N, S co-doped bifunctional carbon catalyst for sustainable fixation of CO2 to cyclic carbonates. Issue 4 (1st February 2022) - Ghosh, Anindya; Reddy, G. Naaresh; Siddhique P. K., Mohammed; Chatterjee, Sauvik; Bhattacharjee, Sudip; Maitra, Rahul; Lyubimov, Sergey E.; Arzumanyan, Ashot V.; Naumkin, Alexander; Bhaumik, Asim; Chowdhury, Biswajit
Abstract : Compositional doping by nitrogen and sulfur into a carbon matrix with a distinct hollow sphere architecture was achieved via a simple approach and the co-doped carbon material was used as a bifunctional catalyst for an efficient CO2 –epichlorohydrin cycloaddition reaction. Abstract : Execution of compositional doping by more than one element simultaneously inside a carbon matrix is a challenging task for designing advanced carbon-based materials and nanotechnology. Herein, we have integrated a template-free methodology for the preparation of a hollow sphere N, S co-doped carbon material utilizing melamine and p -toluenesulfonic acid as a nitrogen and sulfur precursor, highlighting a cost-effective, simple, and green process. This N, S dual doped carbon material acted as a promising bifunctional catalyst for sustainable CO2 fixation to form a cyclic carbonate with an epoxide, and this strategy is appealing for the conversion of CO2 to chemicals. The as-synthesized catalyst was comprehensively characterized by FESEM and HRTEM techniques, showing that the formed nanosheets arranged randomly in the shape of a sphere and turned out to be a hollow sphere after carbonization. The XPS analysis revealed that the randomly arranged nanosheets are linked via –C–S–S–C– linkages. The abundance of weakly acidic and basic sites helps to achieve very high activity (GC conversion 95% and selectivity 98%) in a CO2 –epichlorohydrin cycloaddition reaction at 343 K temperature in the presence of a co-catalyst. The experimental results coupled with the theoretical adsorption energy calculation led us to propose that majorly the CO2 molecule gets adsorbed on the pyridinic N species while epichlorohydrin prefers a terminal –SO2 H acidic site for adsorption. Additionally, the DFT study elucidated the detailed reaction mechanism for the CO2 –epichlorohydrin reaction and identified the attack of CO2 by the iodoalkoxy anion as the rate-determining step. Beneficially, this study establishes a definitive relationship between CO2 utilization and an advanced heteroatom doped carbon-based catalyst.